Identifying Elements to Implement E-Ââ€Governance: Role of Organizational Readiness, Authority Readiness, Customer Readiness, Competency Readiness and Technology Readiness - Valliappan Raju, Assoc. Prof. Dr.; Siew Poh Phung, Dr.; Ramanathan Kalimuthu, Prof. Dr. (International Journal of Engineering and Technology, 2019)
In this research paper, the main purpose is to investigate the concept of structural display for e-Government Readiness Assessment (ERA). In the paper, six major elements are identified as those that play a crucial role in executing e-Government activities. Before propelling e-activity, it becomes important to consider such fundamental variables that play predictive roles relative to the ability to implement practices while abiding by certain prescribed regulations. In the study, major variables that have been investigated include legal readiness, technology readiness, competency readiness, customer readiness, government and authority readiness, and organizational readiness. From the perspective of organizational statuses, the paper examines an e-Government bureaucratic nature, long process deferrals, and business processes. Regarding the attributes of leadership and governance readiness, it is imperative to note that various parameters have been assessed. These parameters include the responsibility for open occupations, how authorities perform, the benefit of understanding, and the significance of e-activity administration and authority. From the perspective of customer attributes, a major focus involves principles of security, trust, and openness. Regarding the competency status, a major consideration under examination involves a reducing number of qualified workforces, as well as some of the diverse strategies through which this issue could be addressed. Another notable feature involves technology preparation and implementation in which major issues under examination include the establishment of secure trade administration foundations, information and application sharing, inheritance frameworks, current innovation, correspondence, programming, and equipment. Finally, the attribute of legal preparation has been examined relative to the Malaysian Temporary Law No. 85â€™s 2011 appropriation has gained in-depth analysis; especially in relation to the adoption of e-activity and security. Overall, the chief motivation of the paper involves te growing need to gain understanding of the level of readiness towards implementing e-Governance. Â Â Â